Effect of core strength training on Wushu performance: a systematic review - Li, Long; Soh, Kim Geok; Li, Hu; Talib, Othman; Sun, He; Soh, Kim Lam (Gokmen Arslan, 2022)
Core strength training has a conspicuous effect on the performance of Wushu. The primary purpose of this paper is to summarize the effect of core strength training on Wushu Sanda, traditional Wushu routines, and competitive Wushu routines. Heretofore, there is no systematic evaluation report on the performance of Wushu's core strength. Extant literature shows that core strength training can promote the performance of Sanda and set Wushu. However, the lack of influence of core strength training is the most noteworthy challenge associated with competitive Wushu routine. In the current literature, there are insufficient conclusions on the influence of core strength training on Wushu performance. In recent years, the development direction of competitive Wushu routines has been dominated by high-difficulty movements. If there is a lack of high-difficulty movements in competitive Wushu routines, athletes will not have good results in competitions. This has necessitated a rigorous literature review to evaluate the influence of core strength training on the performance of Wushu.